The situation of the tourist sectors after the outbreak of the COVID-19 pandemic - tourism covidisation. (8th November 2022) - Korinth, Bartosz
The article puts forward a proposal for a new concept enabling a more in-depth analysis of the impact of the development of the COVID-19 pandemic on the tourism sector, dating back from the turn of 2019 and 2020. In order to present the concept of 'tourism covidisation', subject literature has been analysed. While analysing the literature, it was found that the spread of the COVID-19 pandemic has affected all tourism sectors: the accommodation and catering sector, the tourist attractions sector, the transport sector as well as the tourism organisers sector. This prompted the author of this publication to create a new definition - tourism covidisation, which may be defined as "any effects on the tourism industry sector directly or indirectly connected to the COVID-19 pandemic."